Integration Factors of Green Skills into Building Construction Trade Programme in Nigeria - Hamza, Samaila; Musta'amal @ Jamal, Aede Hatib; Kamin, Yusri Bin (Journal of Technical Education and Training, 2020)
Technical and vocational education and training (TVET) remains a vital tool for skilling young individuals both in and out of school. However, it appears that there has been a lack of research especially in the building construction sector with respect to green buildings in Nigeria. The main purpose of this research paper is to identify factors should be included in the greening of building construction trade curriculum of technical colleges in north western Nigeria with a view to improving teaching and learning green skills for sustainable development. In this study, simple random sampling was used to select 15 building construction teachers in the north western Nigerian technical colleges. Data for this study were collected using qualitative approach (that is interview). Respondents were requested to answer the interview questions based on the topic under study. The factors (data) identified from the perception of the respondents were collected and analysed by qualitative means based on their level of  consideration with regards to improving teaching and learning green skills for sustainable development. In doing so, the data were analysed by transcription, coding, content analysis and thematic with the aid of Nvivo statistical software. Findings indicated that the three main factors that could be included in the integration of green skills into the curriculum of building construction trade include environmental, economic and social factors. Specifically, these factors were disintegrated into climate change, global warming, greenhouse gas emission, economic instability, health and safety issues related to buildings, waste and energy in buildings. This research forms the initial investigation of a more in-depth study of the green skills integration into the Nigerian education curriculum, which aims to achieving environmental, economic and social sustainability.